Incidence, Risk Factors, and Modified Risk Assessment Model of Venous Thromboembolism in Non‐Hodgkin Lymphoma Patients - Wen Li; Rui Liu; Ying Shen; GongZhizi Gao; Rui Yang; Yiwen Wang; Ruoyu Yang; Zujie Lin; Ruijun Dong; Wanhong Zhao; Aili He; Ju Bai (Cancer Medicine)
ABSTRACT Background Venous thromboembolic events (VTEs) are the second‐leading cause of death in cancer patients, with an incidence of 5%–17% in lymphoma patients, particularly higher in those with non‐Hodgkin lymphoma (NHL). Existing risk assessment models (RAMs) like the Khorana and ThroLy scores have limitations and are inadequately validated for NHL patients. Coagulation markers such as D‐dimer, thrombin–antithrombin complex (TAT), and thrombomodulin (TM) show a potential predictive value for cancer‐associated VTE but lack extensive research in NHL. Objectives This study aimed to analyze characteristics and predictive risk factors for VTE in newly diagnosed NHL patients and to evaluate and improve the clinical applicability of the Khorana and ThroLy scores. Methods Data were collected from newly diagnosed NHL patients to analyze characteristics and potential predictive risk factors for VTE. The clinical applicability of the Khorana and ThroLy scores was evaluated, and the ThroLy score was improved by adjusting the hemoglobin cutoff and combining it with D‐dimer testing. Sequential testing with TM and TAT levels was also performed. Results VTE developed in 7.09% of NHL patients. Independent risk factors for VTE included clinical Stage III/IV, mediastinal involvement, history of VTE, D‐dimer≥ 1345 μg/dL, and platelet (PLT)≥ 298 × 109, and Hb≥ 110 g/L was an independent protective factor for VTE. The ThroLy score was improved by adjusting the hemoglobin cutoff and combining it with D‐dimer testing. Sequential testing of TM and TAT achieved a sensitivity of 66.7%, specificity of 100%, positive predictive value (PPV) of 100%, and negative predictive value (NPV) of 96.7%. Conclusions VTE is a significant complication in NHL patients. The study highlighted independent risk factors and proposed a modified risk assessment model that effectively predicted VTE risk, potentially optimizing prevention and reducing healthcare costs.